Ionic liquid pretreatment at high solids loading: A clean approach for fabrication of renewable resource based particulate composites - Mahmood, H. (John Wiley and Sons Inc., 2018)
Recently, the concept of high solids loading in ionic liquid (IL) based pretreatment of lignocellulosic biomass has gained numerous attention due to significant economic, environmental, and sustainability benefits. The objective of the present work was to investigate the impact of ILs pretreatment of lignocellulosic oil palm frond (OPF) biomass at high solids loading on the mechanical and thermal properties of the composite panels. The process combines the pretreatment of OPF particles with ILs bmimCl (1-butyl-3-methylimidazolium chloride) and emimOAc (1-ethyl-3-methylimidazolium acetate) followed by IL recovery by rinsing with acetone-water mixture prior to mixing of OPF particles with polymer binder to fabricate compression-molded composite panels. Untreated and treated OPF particles were characterized by scanning electron microscopy, X-ray diffraction, thermogravimetric analysis, and chemical composition analysis. Further, the effect of ILs pretreatment on kinetics of thermal degradation of biocomposites was evaluated by activation energy approach. Maximal flexural strength, modulus, and strain energy density (SED) of 25 MPa, 1,928 MPa, and 0.48 MJ/m3, respectively, were found for IL emimOAc treated composite. Besides, thermal properties of IL treated composites were also improved. Present study could be a significant step toward practical IL pretreatment strategies for manufacturing of lignocellulosic based composite materials. POLYM. COMPOS., 39:1994â2003, 2018. Â© 2016 Society of Plastics Engineers. Â© 2016 Society of Plastics Engineers